The Effect of Parental Role, Learning Discipline, and Achievement Motivation on Learning Outcomes of Elementary Mathematics - Rusmini, Mas Ayu; Ariawan, I Putu Wisna; Tatminingsih, Sri (Universitas Wiralodra, 2024)
This study aims to determine the influence of the role of parents, learning discipline and achievement motivation on the learning outcomes of students in grade 4 elementary school. The population in this study were 59 students. The research sample consisted of 51 students who were determined by proportional random sampling technique, namely taking samples from members of the population randomly and proportionally stratified. Data on the role of parents, learning discipline and student achievement motivation were collected using a questionnaire while data on mathematics learning outcomes were collected from document records. Data were analyzed using simple correlation test and multiple correlation. with the help of the SPSS 25.0 for Windows program. The results showed that: (1) there was a significant effect between the role of parents on students' mathematics learning outcomes as indicated by a Sig value of 0.00 <0.05. (2) there is a significant effect between learning discipline on students' mathematics learning outcomes indicated by the value of sig = 0.000 <0.05. (3) There is a significant effect between achievement motivation on students' mathematics learning outcomes as indicated by the sig = 0.000 <0.05. (4) Simultaneously, there is an effect between the role of parents, learning discipline and achievement motivation on the learning outcomes of elementary mathematics with a significance result of 0.000 <0.05. So, it can be concluded that there is an effect between the role of parents, learning discipline and achievement motivation on learning outcomes in elementary school mathematics.